PENAMBAHAN SUSU BUBUK FULL CREAM PADA PEMBUATAN PRODUK MINUMAN FERMENTASI DARI BAHAN BAKU EKSTRAK JAGUNG MANIS [Addition of Full Cream Milk Powder in the Production of Fermented Drink Made from Sweet Corn Extract] - Hartati Chairunnisa (Departemen Ilmu dan Teknologi Pangan, IPB Indonesia bekerjasama dengan PATPI, 2009)
The aims of this study were to determine the effect of full cream milk powder addition to the quality of fermented drink from sweet corn extract. The quality examined were total bacteria, total solid, lactic acid content, and acceptability including colour, texture, flavor, and overall acceptance. The experiment was set up in a Completly Randomized Design with five levels of full cream milk powder (8, 10, 12, 14, 16%) and four replications. The results showed that addition 12% of full cream milk powder in sweet corn extract resulted in acceptable fermented drink containing of 11.2 x 109 cfu/g lactic acid bacteria, 17.8% total solid, and 0.95% lactic acid. This formula had yellow color, desired texture & flavor and recieived the highest score of overall acceptance.